Productive objects: An applied software project management framework - Robert J Muller (Morgan Kaufmann, 1998)
The book provides an integrated, cohensive system of project management that aligns directly with the technology it manages, the methods necessary to productively manage object-oriented software development; It also contains real-work examples that illustrate how all of the different objects work